Literature Review of Slingshot Games and Its Potential Application in Learning Physics - Heny Aryani; Nurita Apridiana Lestari; Budi Jatmiko; Alfi Nurlailiyah; Arie Realita; Antomi Saregar; Utama Alan Deta (Reog: Journal of Ecoethnoscience Education, 2026)
Traditional games are part of local wisdom that preserves cultural values and educational potential. One such game is the slingshot, which is not only known as a hunting tool but also incorporates many concepts of physics such as elasticity, potential energy, kinetic energy, and parabolic motion. This study aims to review the literature on slingshots and their relevance in physics education. Data were collected from Scopus-indexed international publications using the keywords “slingshot OR catapult,” yielding 3,013 articles. After applying inclusion criteria and screening based on title, abstract, and keywords, 1,000 articles were selected for analysis using VOSviewer. The results of the study show five main clusters, namely the use of slingshots in aircraft launch, biomechanics, principles in animals, animal experiments, and fundamental aspects of physics. These findings confirm that catapults can be used as a contextual medium in learning to improve understanding of physics concepts and at the same time preserve local culture. By linking indigenous knowledge with scientific principles, this study contributes to enriching physics learning while encouraging the preservation of cultural heritage within modern education.